AN INTEGRATED OMICS APPROACH FOR THE STUDY OF MILD AND SEVERE ALZHEIMER'S DISEASE IN POST-MORTEM HUMAN BRAIN. (16th November 2018) - Graham, S; Yilmaz, A; An, X; Vishweswaraiah, S; Radhakrishna, U; Bahado-Singh, R; Green, B; Maddens, M
Abstract: Background: Alzheimer's disease is 6th leading cause of death in the United States and is its prevalence is continuing to grow with our ever-aging population. Currently the etiology and pathophysiology of the disease is not fully understood making therapy development to slow the progression or stop eth disease difficult. Methods: Using quantitative metabolomic and epigenetic techniques we biochemically profiled post-mortem brain tissue from the neocortex (Brodmann region 7) of people who suffered from cases of mild (n=15) or severe (n=30) Alzheimer's disease (AD) as compared with age- and gender-matched controls (n=30). Results: Using both of these techniques, in combination with bioinformatic analyses, we identified biochemical pathways and some potential central biomarkers previously unreported in AD. Interestingly, we identified lipid metabolism to be the most significantly affected biochemical pathway to be disrupted across the spectrum. Conclusions: Combining two complementary omics technologies offers a more holistic view of the brain metabolome. Brain metabolic responses differ according to disease severity providing clues about how the disease pathology develops. Future studies should investigate the disease mechanisms and the reproducibility of the metabolite biomarkers discovered here.